Multi-Dimensional Composite Frame as Bifunctional Catalytic Medium for Ultra-Fast Charging Lithium–Sulfur Battery - Tian, Shuhao; Zeng, Qi; Liu, Guo; Huang, Juanjuan; Sun, Xiao; Wang, Di; Yang, Hongcen; Liu, Zhe; Mo, Xichao; Wang, Zhixia; Tao, Kun; Peng, Shanglong (Nano-Micro Letters, 2022)
The shuttle effect of soluble lithium polysulfides (LiPSs) between electrodes and slow reaction kinetics lead to extreme inefficiency and poor high current cycling stability, which limits the commercial application of Li–S batteries. Herein, the multi-dimensional composite frame has been proposed as the modified separator (MCCoS/PP) of Li–S battery, which is composed of CoS2 nanoparticles on alkali-treated MXene nanosheets and carbon nanotubes. Both experiments and theoretical calculations show that bifunctional catalytic activity can be achieved on the MCCoS/PP separator. It can not only promote the liquid–solid conversion in the reduction process, but also accelerate the decomposition of insoluble Li2S in the oxidation process. In addition, LiPSs shuttle effect has been inhibited without a decrease in lithium-ion transference numbers. Simultaneously, the MCCoS/PP separator with good LiPSs adsorption capability arouses redistribution and fixing of active substances, which is also beneficial to the rate performance and cycling stability. The Li–S batteries with the MCCoS/PP separator have a specific capacity of 368.6 mAh g−1 at 20C, and the capacity decay per cycle is only 0.033% in 1000 cycles at 7C. Also, high area capacity (6.34 mAh cm−2) with a high sulfur loading (7.7 mg cm−2) and a low electrolyte/sulfur ratio (7.5 μL mg−1) is achieved. Highlights: 1 The presence of Ti–O-Co bonds of the multi-dimensional composite frame separator (MCCoS/PP) promotes kinetics and enables bifunctional catalysis. 2 The existence of MCCoS/PP cannot reduce the lithium-ion transference numbers. 3 The Li–S battery with MCCoS/PP achieves super-high rate (368.6 mAh g−1 at 20C) and ultra-low capacity attenuation rate.